2006
DOI: 10.1148/rg.26si065501
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Imaging of Acute Stroke

Abstract: Stroke is a leading cause of mortality and morbidity in the developed world. The goals of an imaging evaluation for acute stroke are to establish a diagnosis as early as possible and to obtain accurate information about the intracranial vasculature and brain perfusion for guidance in selecting the appropriate therapy. A comprehensive evaluation may be performed with a combination of computed tomography (CT) or magnetic resonance (MR) imaging techniques. Unenhanced CT can be performed quickly, can help identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
202
0
33

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(237 citation statements)
references
References 56 publications
2
202
0
33
Order By: Relevance
“…DWI, while not normally considered as a major dependent variable in research studies, are used clinically as a highly sensitive marker for acute ischemia (Moseley et al, 1990b;Moustafa and Baron, 2007;Srinivasan et al, 2006) and for the evaluation of stroke (Wang et al, 2006). Inspection of DWI, especially in advancing age, reveals a striking conspicuity of the globus pallidus and putamen caused by signal loss in these structures, presumably due to iron accumulation with age.…”
Section: Introductionmentioning
confidence: 99%
“…DWI, while not normally considered as a major dependent variable in research studies, are used clinically as a highly sensitive marker for acute ischemia (Moseley et al, 1990b;Moustafa and Baron, 2007;Srinivasan et al, 2006) and for the evaluation of stroke (Wang et al, 2006). Inspection of DWI, especially in advancing age, reveals a striking conspicuity of the globus pallidus and putamen caused by signal loss in these structures, presumably due to iron accumulation with age.…”
Section: Introductionmentioning
confidence: 99%
“…10 The patterns of hypoperfusion in acute brain infarction have been described. 11 MR perfusion abnormalities have also been described in other disorders, (eg, seizures, vasospasm following subarachnoid hemorrhage, and severe stenosis of intra-or extracranial vessels). 12,13 MR imaging, nuclear medicine, and CT perfusion studies have demonstrated that migrainous aura may be associated with perfusion abnormalities; however, all articles are limited to a small number of selected patients.…”
mentioning
confidence: 95%
“…CT perfusion is a functional imaging technique that can be used to identify salvageable brain tissue [1,2]. Diffusion-weighted MR imaging can be used for identifying infarcted brain tissue that is irreversibly damaged, whereas perfusion-weighted MR imaging can be used for identifying reversibly injured ischemic brain tissue [3]. Although CT and MR are versatile imaging modalities that are capable of depicting various aspects of acute stroke-associated brain changes, their actual usage at a particular institution depends to a large extent on the availability of equipment and the experience and expertise level of that institution.…”
Section: Introductionmentioning
confidence: 99%